Investigating the effects of signal light position on human workload and reaction time in human-robot collaboration tasks - Johnson, Teegan L.; Fletcher, Sarah R.; Webb, Philip (Springer, 2016)
Critical to a seamless working relationship in human-robot collaborative environments is effective and frequent communication. This study looked to assess whether placing a light source on a robot was more effective for informing the human operator of the status of the robot than conventional human-machine interfaces for industrial system signaling such as light towers. Participants completed an assembly task while monitoring a robot and changes to the light sources: either from one of two light towers or LED strip lights attached to the robot. Workload was assessed by measuring reaction times to light changes and by counting number of completed assemblies. Although both the ANOVA and Friedman tests returned none significant results, total misses per condition showed that the participants did not miss any of the robot lights, whereas signals were missed for the light towers.
Keywords: Human-robot communication; Collaboration; Human factors; Eye tracking